Evidence-based training recommendations for the elite judoka - Harris, D. M.; Foulds, S.; Latella, C. (Strength and Conditioning Journal, 2019)
There is a paucity of sport-specific evidence regarding strength and conditioning strategies to improve elite judo athletes' (eja) performance. Therefore, the aim of this article is to evaluate the current literature and present evidence-based training recommendations for eja. Based on the sport-specific demands, appropriately sequenced periodized strength and conditioning programs that include (a) heavy strength training, (b) power training (i.e., contrast loading, cluster sets, weightlifting, and plyometric exercises), and (c) high-intensity interval training may provide sufficient stimuli to improve upper- and lower-body strength, aerobic and anaerobic power for eja.